"An investigation on DMFTand DMFS of first permanent molars in 12-year- old blind children in residential institutes for blinds in Tehran (2000-2001) " - M. Ghandehari Motlagh; A. Kohestani (Tehran University of Medical Sciences, 2004)
Statement of Problem: Blindness as a disability seems to produce difficulties to reach an ideal heath status of the teeth. Moreover ordinary educational health programmes for this group of population, especially children, are not successful. Purpose: Investigate the dental health status of these children and to see if they are really different with the normal population. Materials and Methods: All sixty three 12- year- old blind children in three institutes were studied. A general questionnaire, as well as a dental questionnaire including some information on the first molars, were completed by these children. Results: The average DMFT and DMFS of the first molars were 3.30± 1.19 and 6.22±3.95 respectively. DMFT was higher in the lower molars, Compared with to the upper ones. However, DMFS was higher in the upper molars. Conclusion: The present study shows that the values of these indices, among blind children, are close to those of normal population, indicating that under controlled health condition and good education, acceptable values for DMFT and DMFS will be obtained.